Development of Surface Plasmon Resonance-Based Immunosensor for Detection of Brucella melitensis - Saberi,Fatemeh (2016)
A label-free optical immunosensor was developed based on surface plasmon resonance (SPR) method for rapid and selective detection of Brucella melitensis. This immunosensor was constructed by immobilizing capture antibody on 11-mercaptoundecanoic acid modified gold disk. This fabricated immunosensor detected B. melitensis at a concentration range from 103 to 107 cell mL-1 (R2 = 0.998) and a detection limit of 100 cell mL-1. Additionally, the kinetic equilibrium dissociation constant (KD) for assessment of the interaction affinity was calculated as 1.1 × 10-9 mol L-1 that can be considered as high affinity interaction. This SPR immunosensor provided advantages in term of fast response, label free and accurate detection of B. melitensis in analytical systems.